TAFSIR KONTEKSTUAL TUJUAN PERNIKAHAN DALAM SURAT AR-RUM: 21 - Mohammad Fauzan Ni'ami (Nizham Journal of Islamic Studies, 2022)
Abstract This paper discusses the contextualization of the purpose of marriage contained in the letter Ar-Rum verse 21. It starts by examining the text of the verse using the lughowiyah rules, then the internal context of the verse, the interpretation of the verse according to the Salaf and Khalaf scholars, which then analyzes the understanding of the letter ar-rum: 21 in the current context. This is done to seek a complete understanding of the purpose of marriage in the present context. This paper is included in library research using the descriptive-qualitative method using the contextual interpretation analysis method. This paper shows that the purpose of marriage contained in the letter Ar-Rum verse 21 is not just a reproductive function, but has a wider scope, such as economic improvement, intellectual-moral improvement, and activation of protection. Keyword: Purpose of Marriage, Contextual, Ar-Rum: 21 Abstrak Tulisan ini membahas mengenai kontekstualisasi tujuan pernikahan yang terdapat dalam surat ar-Rum ayat 21. Dimulai dengan menelaah teks ayat tersebut dengan menggunakan kaidah lughowiyah, kemudian konteks internal ayat, tafsir ayat menurut ulama salaf dan kholaf, yang kemudian analisis pemahaman surat ar-rum: 21 dalam konteks saat ini. Hal ini dilakukan untuk untuk mencari pemahaman secara utuh mengenai tujuan pernikahan pada konteks kekinian. Tulisan ini termasuk dalam kajian kepustakaan (library research) dengan menggunakan metode deskriptif-kualitatif dengan menggunakan metode analisis tafsir kontekstual. Tulisan ini menunjukan tujuan pernikahan yang terdapat pada surat ar-Rum ayat 21 bukan sekedar sebagai fungsi reproduksi saja, melainkan cakupanya lebih luas, seperti halnya peningkatan ekonomi, peningkatan intelektual-moral, dan aktivasi perlindungan. Kata Kunci: Tujuan Pernikahan, Kontekstual, Ar-Rum: 21